1996
DOI: 10.1046/j.1365-3059.1996.d01-188.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of formulated rhizobacteria against root rot of field pea

Abstract: Formulations of bacterial biocontrol agents were evaluated for the control of pea root‐rot caused primarily by Pythium ultimum and Rhizoctonia solani, at different levels of disease severity in field trials. Pseudomonas fluorescens (strain PRA25) in a peat‐based formulation increased yield by 17% over the untreated, in a trial with light disease infection, and by 120% in another with moderate infection. Other bacteria including P. cepacia (strain AMMD) and fluorescent pseudomonads increased seedling emergence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This strain was isolated from apparently healthy pea plants in Wisconsin (USA) in 1985. Several studies have shown that strain LMG 19182 is very effective in controlling phytopathogenic Pythium species (responsible for preand post-emergence damping-off in peas) (Parke, 1990 ;Parke et al, 1991 ;Xi et al, 1996) and Aphanomyces euteiches (responsible for root-rot and the main factor limiting pea production in the American Midwest) (King & Parke, 1993). In an ongoing survey of B. cepacia-like isolates by means of whole-cell protein analysis, amplified fragment length polymorphism (AFLP) fingerprinting and sequence analysis of the recA gene, 18 isolates from human clinical and environmental specimens exhibited similarity towards B. cepacia LMG 19182.…”
Section: T Coenye and Othersmentioning
confidence: 99%
“…This strain was isolated from apparently healthy pea plants in Wisconsin (USA) in 1985. Several studies have shown that strain LMG 19182 is very effective in controlling phytopathogenic Pythium species (responsible for preand post-emergence damping-off in peas) (Parke, 1990 ;Parke et al, 1991 ;Xi et al, 1996) and Aphanomyces euteiches (responsible for root-rot and the main factor limiting pea production in the American Midwest) (King & Parke, 1993). In an ongoing survey of B. cepacia-like isolates by means of whole-cell protein analysis, amplified fragment length polymorphism (AFLP) fingerprinting and sequence analysis of the recA gene, 18 isolates from human clinical and environmental specimens exhibited similarity towards B. cepacia LMG 19182.…”
Section: T Coenye and Othersmentioning
confidence: 99%
“…Biofertilizers containing symbiotic N 2 -fixing R. leguminosarum and phosphate-solubilizing microorganisms, such as Nodulator1 (Becker Underwood Inc., Saskatoon, Saskatchewan) and Tag Team1 (Philom Bios Inc., Saskatoon, Saskatchewan), are recognized as beneficial inputs by Western Canadian pea and lentil growers. Xi et al (1996) reported that several fluorescent pseudomonads and Pseudomonas spp. strains PRA25 and AMMD were antagonistic to the pea root rot pathogens Pythium ultimum and Rhizoctonia solani in field trials in Saskatchewan.…”
Section: Introductionmentioning
confidence: 99%
“…The microorganisms identified as potential bioagents include Bacillus subtilis (Ehrenberg) Cohn (Hwang and Chakravarty 1992), nonpathogenic Fusarium oxysporum (Oyarzun et al 1994), Gliocladium virens Miller, Giddens, and Foster [syn. Trichoderma virens (Miller et al) von Arx] (Hwang and Chakravarty 1993), Penicillium oxalicum Currie & Thom (Windels and Kommedahl 1978), Pseudomonas cepacia Palleroni & Holmes and P. fluorescens Migula (Parke et al 1991;Xi et al 1996), Trichoderma hamatum (Bon.) Bain.…”
Section: Discussionmentioning
confidence: 99%